Application of the direct sire comparison method to the Finnish dairy cattle population - Syväjärvi, Jouko; Ojala, Matti; Hellman, Tapani (Agricultural and Food Science, 1983)
Data, consisting of a total of 400542 first lactation records completed in 1975 through 1982, were utilised for development of a model for ranking sires. Using the principle of direct sire comparison method(BLUP), sire evaluations were calculated assuming three models. Model 1 included random terms for sires and maternal grandsires (MGS) of cows, fixed sire and MGS groups within the three breeds and fixed two-year classes within herds. A two-year period within a herd was used to increase the number of records in a class. In model 2 genetic groups were only for breeds. Model 3 included fixed breed groups and herd-year classes. Relationships among bulls were used in all models. About 83, 13 and 2 % of cows making the records were of the Finnish Ayrshire (FAy), the Finnish Friesian (FFr) and the Finncattle (Fc), respectively, while about 2 % were of various crossbreds. About 20 % of the herd-year classes had cows of more than one breed. Practically all of the male ancestors of bulls and about 70 to 85 % of maternal grandsires of cows were identified in recent years. About 7 % of the total variation for fat corrected 305-day milk (FCM) production was accounted for by years within herds. The fraction of records lost in editing was 4 % for models 1 and 2, and 11 %for model 3. Assuming model 3, the average numbers of daughters for bulls of the FAy-, FFr- and Fc-breeds were 130, 152 and 44, respectively. Average number of records in a herd-year class was about 3.6 in recent years. The additive genetic superiority of the FAy-breed in FCM-production to the FFr- and Fc-breeds was 84 and 860kg, respectively. Joint use of bull groups and relationships among males (model 1) tended to underevaluate the youngest bulls and overevaluate the oldest bulls belonging to previous generations. Based on the results and the breeding structure in theFinnish dairy cattle population, model 3 was chosen to be used in official sire evaluation.